REASONS FOR THE FORMATION OF RADIONUCLIDES IN THE SOIL AND RADIOECOLOGICAL CONDITIONS IN THE OIL FIELDS (IN ABSHERON PENINSULA) - ALIYEV, Chingiz; KAZIMOVA, Latifa (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is known that oil and gas are the main priority of the production and processing industry in Azerbaijan. Considering that the development and operation of oil fields, processing of oil and oil products are the main pollutant of the environment, the Absheron Peninsula is considered the most environmentally tense region of Azerbaijan. The purpose of our research is to study the radioecological situation and assess the level of radioactive contamination of the soil of the Absheron Peninsula. As a rule, radium concentration occurs at the surface of the reservoir and during the initial treatment of the water mixture. For example, radium deposition is generally observed on land where oil equipment is located and on areas where the reservoir water is close to the surface or is exposed. The first studies of radioactivity on the territory of the Absheron Peninsula were carried out in 1930-32. The purpose of these studies was to search for radium in soils, groundwater. At that time, high levels of radium were found in the waters of some oil fields. There was little uranium in the waters and oils of these deposits. In our work the distribution of radioactivity on the territory of the Absheron Peninsula was studied and the most dangerous areas for human activity were identified. A radioactivity map of the study area was created to study the radioactive background and identify dangerous areas. As a result of our research, it was found out that most of the polluted part of the Absheron Peninsula is an industrial oil production zone. Based on our materials, a radioactivity map for the study area was created. In the article, not only the radiation background of the Absheron peninsula, thus determining the areas with the average value of the radiation background at 8.5 µR/h but also the areas where it equaled 400-600 µR/h that is, the dangerous levels for living and working are shown. We have highlighted anomalies where radioactivity reaches 400-600 µR/h.
Keywords: landscape; exposure dose; Absheron; radon; oil